2019
DOI: 10.1186/s13031-019-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Treating Syrian refugees with diabetes and hypertension in Shatila refugee camp, Lebanon: Médecins Sans Frontières model of care and treatment outcomes

Abstract: Background Médecins Sans Frontières (MSF) has been providing primary care for non-communicable diseases (NCDs), which have been increasing in low to middle-income countries, in the Shatila refugee camp, Beirut, Lebanon, using a comprehensive model of care to respond to the unmet needs of Syrian refugees. The objectives of this study were to: 1) describe the model of care used and the Syrian refugee population affected by diabetes mellitus (DM) and/or hypertension (HTN) who had ≥ one visit in the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 23 publications
6
70
2
Order By: Relevance
“…The burden of NCDs is growing swiftly among Syrian refugees in Lebanon and the region (43). Previous studies found a high prevalence of reported hypertension, diabetes, CVDs and other NCDs amongst Syrian refugees in Lebanon (43,44), and prevalence was most pronounced among adults above 40 (45). One study indicated that the prevalence rates reached 21% for hypertension, 11% for CVDs and 10% for diabetes (46).…”
Section: Aspects Of Ncds Among Syrian Refugees In Lebanonmentioning
confidence: 99%
See 4 more Smart Citations
“…The burden of NCDs is growing swiftly among Syrian refugees in Lebanon and the region (43). Previous studies found a high prevalence of reported hypertension, diabetes, CVDs and other NCDs amongst Syrian refugees in Lebanon (43,44), and prevalence was most pronounced among adults above 40 (45). One study indicated that the prevalence rates reached 21% for hypertension, 11% for CVDs and 10% for diabetes (46).…”
Section: Aspects Of Ncds Among Syrian Refugees In Lebanonmentioning
confidence: 99%
“…Although the prevalence of NCDs among the Syrian refugee population in Lebanon has reached alarming rates and regardless of the presence of healthcare actors to respond to the needs of the refugee population, very little is being done to control and manage these costly diseases which remain to be a heavy burden within this population (44).…”
Section: Aspects Of Ncds Among Syrian Refugees In Lebanonmentioning
confidence: 99%
See 3 more Smart Citations